2009
DOI: 10.1158/1078-0432.ccr-08-2113
|View full text |Cite
|
Sign up to set email alerts
|

Short Pigment Epithelial-Derived Factor-Derived Peptide Inhibits Angiogenesis and Tumor Growth

Abstract: Purpose: Pigment epithelial-derived factor (PEDF) is a potent angiogenesis inhibitor with multiple other functions, some of which enhance tumor growth. Our previous studies mapped PEDF antiangiogenic and prosurvival activities to distinct epitopes. This study was aimed to determine the minimal fragment of PEDF, which maintains antiangiogenic and antitumor efficacy. Experimental Design: We analyzed antigenicity, hydrophilicity, and charge distribution of the angioinhibitory epitope (the 34-mer) and designed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 29 publications
(41 reference statements)
1
52
1
1
Order By: Relevance
“…There is accumulating evidence that overexpression of Cav promotes tumor growth and metastasis of prostate cancer via diverse pathways (3)(4)(5)(6), while PEDF may protect against the progression of prostate cancer, via anti-angiogenic, anti-inflammatory and proapoptotic effects (17)(18)(19). To the best of our knowledge, the present study demonstrated for the first time that treatment with 1 or 10 nM PEDF significantly inhibited the Cav-induced increase in IL-8 mRNA expression in PC-3 (17).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…There is accumulating evidence that overexpression of Cav promotes tumor growth and metastasis of prostate cancer via diverse pathways (3)(4)(5)(6), while PEDF may protect against the progression of prostate cancer, via anti-angiogenic, anti-inflammatory and proapoptotic effects (17)(18)(19). To the best of our knowledge, the present study demonstrated for the first time that treatment with 1 or 10 nM PEDF significantly inhibited the Cav-induced increase in IL-8 mRNA expression in PC-3 (17).…”
Section: Discussionsupporting
confidence: 54%
“…PEDF has been identified as a highly effective inhibitor of angiogenesis in cell culture models as well as in animal models (11,12). Furthermore, studies have demonstrated that PEDF blocks cytokine-induced and vascular endothelial growth factor-induced angiogenesis and inflammatory reactions, inhibits tumor growth and induces apoptosis in tumors, including prostate cancer (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Our group has recently demonstrated that PEDF binds to Cav and blocks its pro-inflammatory effects in endothelial cells (25).…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study, smaller regions of 34-mer epitope (named P14, P18 and P23, according to their respective length) were tested for angioinhibitory activity in vitro and in vivo. P14 and P23 display antiangiogenic activity in vitro (both blocking endothelial chemotaxis, and inducing apoptosis in the case of P23), but not in vivo; while P18 is a more potent antiangiogenic peptide than 34-mer in prostate cancer, being able to block bFGF and VEGF-dependent angiogenesis in the in vivo cornea neovascularisation assay (Mirochnik et al, 2009). Another study by Ek and colleagues identified other small peptides with antitumoral activity in an orthotopic osteosarcoma model.…”
Section: Therapeutic Applications Of Pigment Epithelium Derived-factormentioning
confidence: 99%
“…Essentially, PEDF has been determined to be the most potent endogenous angiogenic inhibitor in the body with the ability to prohibit neovascularization in the cornea, as well as endothelial cell growth, tumour proliferation and cancer metastasis [17,20]. Furthermore, PEDF has also been found to promote neuronal survival and cellular differentiation [21,22]. …”
Section: Introductionmentioning
confidence: 99%